'Generative dance' between tacit knowledge, expertise and organisational frameworks. (8th April 2009) - Petricevic, Olga; Houghton, Susan M.
In this paper, we argue that it is critical for both strategy and entrepreneurship scholars to understand the competing choices that knowledge-holders face for deploying their knowledge and ultimately creating and appropriating value within: (1) established organisational structures, (2) new ventures or (3) market exchange. We explore the value creation options from individuals' tacit knowledge and expertise within a dynamic context, arguing that primarily through the 'generative dance' between tacit knowledge, expertise and combinatory assets of organisational frameworks will the knowledge-based value creation unfold over time. The level of configurations of knowledge-based assets and other organisational combinatory assets will impact the distribution of gains and the share the knowledge-holder will extract from generated economic rents. We shift the focus to the source of the value (i.e. the knowledge-holder) and pose the question: 'Who benefits most from the value generated from tacit knowledge and expertise?'